Impact of mechanical simulator practice on clinical ERCP performance by novice surgical trainees: a randomized controlled trial - Meng, Wenbo; Yue, Ping; Leung, Joseph W.; Wang, Haiping; Wang, Xiyan; Wang, Fangzhao; Zhu, Kexiang; Zhang, Lei; Zhu, Xiaoliang; Wang, Zhengfeng; Zhang, Hui; Zhou, Wence; Li, Xun (Endoscopy, 2020)
Background Lack of forward-viewing endoscopy experience impairs training in endoscopic retrograde cholangiopancreatography (ERCP). We evaluated the effect of ERCP mechanical simulator (EMS) practice on ERCP performance by surgical trainees.Patients and methods 12 surgical trainees without endoscopy experience were randomly allocated to non-EMS (n = 6) programs or to EMS (n = 6) programs with coaching and 20 hours of supervised EMS practice. All trainees then received supervised hands-on clinical ERCP training. Trainers provided verbal instructions and hands-on assistance, and took over if cannulation was not achieved by 20 minutes. Blinded trainers rated clinical performance. Results Each group performed 150 clinical ERCPs. Biliary cannulation success was significantly higher in the EMS vs. the non-EMS group (P = 0.006), with shorter mean times (in minutes) for intubation, cannulation, and completion (all P < 0.001). EMS trainees showed a significantly better mean performance score (P = 0.006). In multivariate analysis, after adjusting for case sequence, CBD stone, complexity, and EMS training, the effect of EMS practice on odds for successful cannulation remained highly significant (odds ratio [OR] 2.10 [95 %CI 1.46 – 3.01]). At 6 months EMS trainees still had better cannulation success vs. non-EMS controls (P = 0.045); no difference was observed after 1 year.Conclusions EMS practice shortens the ERCP early learning curve of inexperienced surgical trainees, improves clinical success in selective biliary cannulation, and may reduce complications.